Preparation of Ni coating on NdFeB by magnetic jet electrodeposition. (July 2019) - Jiang, Wei; Shen, Lida; Qiu, Mingbo; Fan, Mingzhi; Wang, Xin; Tian, Zongjun
In order to lengthen the lifespan of NdFeB materials, nickel coating was manufactured by magnetic jet electrodeposition. The surface morphology, coating adhesion, and corrosion resistance of the coating were characterized and analyzed, respectively, by scanning electron microscope, scratch tester, and electrochemical workstation. The experimental results show that the surface of nickel coating which was fabricated by magnetic jet electrodeposition had no nodularity, and as a result, the surface morphology improved; furthermore, the corrosion resistance and coating adhesion of the coating improved in the effect of magnetic field intensity. When the value of the current density was 60 A/dm 2 and the intensity of magnetic field was 100 mT, the coating adhesion could reach the standard in 33.4 N, which was doubled compared to the coating without magnetic field. Corrosion of the coating morphology is no longer the regional corrosion. Magnetic field is beneficial to improve the quality of coating surface morphology and reduce the corrosion current density of the coating.